SOME FEATURES OF IMPLEMENTING CIRCULAR ECONOMY IN CHINA (Marketing Journal, 2025)
. The article analyzes the integration of the circular economy in China, which will define new challenges in relation to an effective sustainable development strategy focused on minimizing waste and maximizing the use of resources. Of particular importance a re such key factors of economic development as the consolidation of resource potential in priority areas in the context of the reformatting of the global economic architecture. The authors note that an integral tool in the implementation of joint waste rec ycling projects is the creation of an eco -civilization, which promotes industry based on new technologies, urbanization, and modernization of agriculture. Thus, there is a need to develop a unified methodological basis for assessing the effectiveness, payb ack, and risks of implementing innovative projects, which can lead to a reduction in environmental pollution and an increase in the efficiency of resource use. The main problems and ways of their resolution are identified. The necessity of developing and u tilizing the potential within the framework of national interests for the deployment of the circular economy in China, Russia, and the Republic of Uzbekistan is substantiated.
Keywords: circular economy; sustainable development; ecology; potential; waste recycling; international cooperation; national interest; eco -civilization; technological innovation; economic growth; China; Uzbekistan